Cytotoxicity Effect of Self-Nanoemulsifying Drug Delivery System from Chloroform Extract of Bay Leaf (Syzygium Polyanthum (Wight) Walp.) with Oleic Acid as a Carrier - Artanti, Anif Nur; Prihapsara, Fea; Rohmani, Sholichah (Indonesian Society for Cancer Chemoprevention, 2022)
Bay leaves are used as food flavoring and also have medicinal properties. They may have cytotoxic effects derived from natural ingredients. The low efficacy of the therapy with an adequate dose preparation of the plant extract is due to its low solubility and oral bioavailability that is less than the maximum. Hence, this study aimed to improve the solubility and oral bioavailability of the extract mainly for the chloroform extract of leaves that are not soluble in water by preparing a self-nanoemulsifying drug delivery system (SNEDDS). Then, the potential cytotoxic effects of the SNEDDS of bay leaves were determined by calculating the value of IC50 on the T47D cell line. The cytotoxic effect of the SNEDDS of bay leaves was determined using an MTT assay, and the findings were read using an ELISA reader. Data analysis is calculated via linear regression methods by using Microsoft Excel software. The results showed that the SNEDDS of bay leaves performed cytotoxic effects on the T47D cell line with IC50 138 μg/mL. The results showed that the optimal composition formula SNEDDS, namely, Tween 20:PG:oleic acid = 2.25:2.25:0.5 in 5 mL SNEDDS preparation, which had a value of transmittance of 83.81% with emulsification time was less than 5 min; the average droplet size was 165.5 nm, and the zeta potential was −0.4 mV. The data analysis showed that the cytotoxicity effect of the SNEDDS of bay leaves is included in the moderate cytotoxic category.Keywords: Bay leaf, optimization, nanoemulsi, cytotoxicity.